2013
DOI: 10.1177/1352458513503052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circulating osteopontin levels in an unselected cohort of patients with multiple sclerosis: relevance for biomarker development

Abstract: Our data do not support a role for circulating OPN levels as a biomarker for disease activity in a heterogeneous clinical setting, but does not rule out a potential role in the cerebrospinal fluid, in a controlled setting such as a clinical trial, or in concert with other biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Osteopontin is present at elevated levels in the plasma of MS patients compared with healthy control subjects [Kivisäkk et al 2014], and at elevated levels in the CSF of MS patients compared with patients with other neurological diseases . Osteopontin is expressed in the lesions of progressive MS patients and has been found to be elevated in the blood [Hur et al 2007] and CSF [Szalardy et al 2013] of MS patients during relapse, decreasing significantly during recovery from relapse [Börnsen et al 2011].…”
Section: Other Effects Of Natalizumab In Rrmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Osteopontin is present at elevated levels in the plasma of MS patients compared with healthy control subjects [Kivisäkk et al 2014], and at elevated levels in the CSF of MS patients compared with patients with other neurological diseases . Osteopontin is expressed in the lesions of progressive MS patients and has been found to be elevated in the blood [Hur et al 2007] and CSF [Szalardy et al 2013] of MS patients during relapse, decreasing significantly during recovery from relapse [Börnsen et al 2011].…”
Section: Other Effects Of Natalizumab In Rrmsmentioning
confidence: 98%
“…Osteopontin is expressed in the lesions of progressive MS patients and has been found to be elevated in the blood [Hur et al 2007] and CSF [Szalardy et al 2013] of MS patients during relapse, decreasing significantly during recovery from relapse [Börnsen et al 2011]. Natalizumab treatment has been shown to decrease osteopontin levels in the CSF ] and plasma [Kivisäkk et al 2014] of RRMS patients. In a study of RRMS patients receiving natalizumab for 2 years, mean plasma osteopontin levels decreased by approximately 31% (p < 0.005), and this decrease correlated with significant (p < 0.005) improvements in mean global cognitive impairment index values [Iaffaldano et al 2014].…”
Section: Other Effects Of Natalizumab In Rrmsmentioning
confidence: 99%
“…For its action in the regulation of immune system, OPN has been recognized to have a role in the development/progression of several autoimmune diseases, such as multiple sclerosis (16,17,18,19) rheumatoid arthritis (20,21), psoriasis (22) and Graves' disease (23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OPN level correlated positively with disease activity and relapse rate [50][51][52][53]. However, there are studies which showed that higher OPN serum level in MS patients is not associated with disease severity [54,55].…”
Section: Multiple Sclerosismentioning
confidence: 92%